Recycling ceramic waste as a raw material in sanitary ware production - T. H. Silva; A. C. M. Castro; F. C. Valente Neto; M. M. N. S. Soares; D. S. de Resende; A. C. S. Bezerra (Cerâmica)
Abstract This study characterized discarded sanitary ware waste (SWW) that could not meet quality requirements. To understand the composition of such SWW, samples were collected, processed, and characterized. This SWW was used to substitute granite in ceramic slips, and the final recycled sanitary ware compositions of 5%, 10%, 25%, 50% and 100% were obtained. Then, the mixtures were evaluated based on density, rheology, linear shrinkage, water absorption, and flexural strength. The results for viscosity and pyroplastic deformation in specimens containing the ceramic waste were better than the reference slip used in a production line. Results for density, water absorption and linear shrinkage showed no significant difference from the control samples. Although the replacement of more than 5% of granite reduced the flexural strength, no tested specimen was below the minimum value required by the industry.